Improving manufacturing processes by value stream mapping in a make to order environment : Case Oilon Oy - von Bagh, Patrik (My University, 2022)
Companies need to develop their manufacturing processes to keep up with the competition of the global industry. Competitiveness is improved by redefining and redesigning the manufactur- ing system. Companies worldwide have implemented the concept of lean to develop their man- ufacturing processes. Lean consists of principles, methods, and tools which eliminate waste and increase the efficiency of processes. Value stream mapping (VSM) is proven to be an effective tool for redefining and redesigning the manufacturing system. A VSM analysis can be applied to a make to order (MTO) environment with a fitted framework. The thesis is conducted as a case study to Oilon Oy. The research question for the thesis is as follows: How can Oilon Oy’s manufacturing processes be developed by value stream mapping? The objectives for the thesis are: 1) define the value stream mapping process, 2) define how the product flows in the current manufacturing process, 3) define the future state of the manufac- turing process, and 4) define the improvements and requirements to achieve the future state. To address these objectives, a VSM analysis is conducted on Oilon Oy’s manufacturing plan in Kokkola, Finland. The theoretical framework of this thesis includes theory of lean and value stream mapping. The theory of VSM consists of conducting a traditional VSM analysis as well as implementing VSM to a MTO environment. The thesis is conducted as a qualitative case study which uses data trian- gulation in validating the data used. Primary data collection methods for the thesis are a litera- ture review, interviews, observation, and workshops. Reports from the case company’s ERP sys- tem are secondary quantitative data that act as a support for the collected primary data. In the results of the study, four phases of the VSM analysis were identified. Each phase included several steps to make a suitable framework for applying it to a MTO environment. The current state of the manufacturing process was defined in the first workshop. 16 different wastes and several additional issues were identified to be impairing the manufacturing flow. The future state was designed and defined in the second workshop event. 16 different terms for the future state were defined. The working plan for the implementation of the future state was planned and defined in the third and final workshop. Following figures present the potential of the future state: production lead time is reduced by 35 %, non-value adding time is reduced by 62 %, the share of value adding time of the production lead time is increased by 13 percentage points, and the value of First Pass Yield is increased by 40 percentage points.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management